Temperature Dependent Phonon Shifts in Single-Layer WS2 - Thripuranthaka, M.; Late, Dattatray J. (Acs Applied Materials & Interfaces, 2014)
Atomically thin two-dimensional tungsten disulfide (WS2) sheets have attracted much attention due to their potential for future nanoelectronic device applications. We report first experimental investigation on temperature dependent Raman spectra of single-layer WS2 prepared using micromechanical exfoliation. Our temperature dependent Raman spectroscopy results shows that the E-2g(1) and A(1g) modes of single-layer WS2 soften as temperature increases from 77 to 623 K. The calculated temperature coefficients of the frequencies of 2LA(M), E-2g(1), A(1g), and A(1g)(M) + LA(M) modes of single-layer WS2 were observed to be -0.008, -0.006, -0.006, and -0.01 cm(-1) K-1, respectively. The results were explained in terms of a double resonance process which is active in atomically thin nanosheet. This process can also be largely applicable in other emerging single-layer materials.
Keywords: layered materials; phonon vibrations; Raman spectroscopy; thermal effect; WS2

Stable field emission from layered MoS2 nanosheets in high vacuum and observation of 1/f noise - Kashid, Ranjit V.; Joag, Pracheetee D.; Thripuranthaka, M.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Nanomaterials and Nanotechnology, 2015)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra-high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nanosheets exhibit more stable field-electron emission in high-vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high-vacuum conditions, attributed to adsorption and desorption processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high-vacuum conditions.
Keywords: Electron emission; layered materials; MoS2; Noise measurement; Raman spectroscopy

Temperature dependent phonon shifts in few-layer black phosphorus - Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Atomically thin two-dimensional (2D) sheets of black phosphorus have attracted much attention due to their potential for future nanoelectronic and photonics device applications. Present investigations deal with the temperature dependent phonon shifts in a few-layer black phosphorus nanosheet sample prepared using micromechanical exfoliation on a 300 nm SiO2/Si substrate. The temperature dependent Raman spectroscopy experiments were carried out on a few-layer black phosphorus sample, which depicts softening of Ag-1 B-2g, and A(g)(2) modes as temperature increases from 77 to 673 K. The calculated temperature coefficients for Ag-1, B-2g, and A(g)(2) modes of the few-layer black phosphorus nanosheet sample were observed to be -0.01, -0.013, and -0.014 cm(-1) K-1, respectively. The temperature dependent softening modes of black phosphorus results were explained on the basis of a double resonance process which is more active in an atomically thin sample. This process can also be fundamentally pertinent in other promising and emerging 2D ultrathin layer and heterostructured materials.
Keywords: black phosphorus; layered materials; phonon vibrations; Raman spectroscopy; thermal effect

Temperature-dependent raman spectroscopy of titanium trisulfide (TiS3) nanoribbons and nanosheets - Pawbake, Amit S.; Island, Joshua O.; Flores, Eduardo; Ramon Ares, Jose; Sanchez, Carlos; Ferrer, Isabel J.; Jadkar, Sandesh R.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Titanium trisulfide (TiS3) has recently attracted the interest of the 2D community because it presents a direct bandgap of similar to 1.0 eV, shows remarkable photoresponse, and has a predicted carrier mobility up to 10000 cm(2) V-1 s(-1). However, a study of the vibrational properties of TiS3, relevant to understanding the electron-phonon interaction that can be the main mechanism limiting the charge carrier mobility, is still lacking. In this work, we take the first steps to study the vibrational properties of TiS3 through temperature-dependent Raman spectroscopy measurements of TiS3 nanoribbons and nanosheets. Our investigation shows that all the Raman modes linearly soften (red shift) as the temperature increases from 88 to 570 K due to anharmonic vibrations of the lattice, which also includes contributions from the lattice thermal expansion. This softening with the temperature of the TiS3 modes is more pronounced than that observed in other 2D semiconductors, such as MoS2, MoSe2, WSe2, and black phosphorus (BP). This marked temperature dependence of the Raman spectra could be exploited to determine the temperature of TiS3 nanodevices by using Raman spectroscopy as a noninvasive and local thermal probe. Interestingly, the TiS3 nanosheets show a stronger temperature dependence of the Raman modes than the nanoribbons, which we attribute to lower interlayer coupling in the nanosheets.
Keywords: 2D semiconductors; layered materials; Raman spectroscopy; thermal effect; TiS3 nanoribbons; TiS3 nanosheets